GAYA KEPEMIMPINAN KEPALA UPT PUSTAKA UNIVERSITAS RIAU DALAM MERAIH AKREDITASI A SELAMA 2 PERIODE PADA TAHUN 2013 DAN 2019 - Vera Miranda; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
UPT Pustaka Riau University has a function as a center for information services, preservation of knowledge, teaching centers, and research centers as well as in order to support the Tri Dharma of Higher Education. In 2013 UPT Pustaka Riau University obtained an A Accreditation certificate until 2019 which was given by the National Library Accreditation Institute (LAP-N) because it had achieved 9 existing component criteria. In 2011 UPT Pustaka Riau University carried out a major improvement both in terms of reading book collections, technology systems, and employee resources, and this was inseparable from the transformational leadership possessed by the head of UPT Pustaka Riau University. The purpose of this research is This study aims to determine the transformational leadership style and its impact on achieving A UPT Pustaka accreditation, Riau University in 2013-2019. This study uses a qualitative approach with a descriptive method. In collecting data, the author uses interview and documentation techniques. The result of this study is that the application of the transformational leadership style of the head of UPT Pustaka, Riau University is quite good. The Head of UPT Pustaka Riau University has a charisma that is able to attract the hearts of his employees in developing and advancing work units, motivating and inspiring employees, giving employees the freedom to innovate in carrying out their duties, and giving appreciation as appreciation to employees. Keywords: Transformational Leadership, Service Innovation, College Libraries, College Accreditation